2017
DOI: 10.1111/spol.12309
|View full text |Cite
|
Sign up to set email alerts
|

The Policymaker's Dilemma: The Risks and Benefits of a ‘Black Box’ Approach to Commissioning Active Labour Market Programmes

Abstract: In September 2009, the British Government launched a new employment assistance model called Flexible New Deal. It was soon replaced by Work Programme in 2011. Both prioritized what is often called a 'black box' approach to public employment assistance, whereby the government purchaser focuses predominantly on outcomes and does not seek to direct agency operations. Using a study of the orientations and strategies of frontline employment services staff in 2008 and 2012, we seek to enhance understanding of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 6 publications
0
38
0
Order By: Relevance
“…In this case, Brandsen and Pestoff's () vision of co‐governance was reflected in a high‐level planning and funding regime that emphasized collaboration and resource sharing based on flexible, locally responsive partnerships. While more market‐oriented forms of governance may have the potential to encourage personalization in specific circumstances, this has not been the experience under many of the UK's large‐scale employability programmes (Considine et al ). We suggest that specific co‐governance arrangements agreed by the funder and partners under MIW established distinctive mechanisms for shared planning and decision‐making that created the conditions for the design of collaborative, personalized street‐level services.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, Brandsen and Pestoff's () vision of co‐governance was reflected in a high‐level planning and funding regime that emphasized collaboration and resource sharing based on flexible, locally responsive partnerships. While more market‐oriented forms of governance may have the potential to encourage personalization in specific circumstances, this has not been the experience under many of the UK's large‐scale employability programmes (Considine et al ). We suggest that specific co‐governance arrangements agreed by the funder and partners under MIW established distinctive mechanisms for shared planning and decision‐making that created the conditions for the design of collaborative, personalized street‐level services.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, part of this critique argues that contracting out employability services to for‐profit companies (which is central to the WP's governance model) reinforces standardization, rather than personalization, as contracted providers seek to minimize variability in services and therefore maximize efficiency (and potentially profits) under ‘payment‐by‐results’ contracting (Lindsay et al ). Considine et al’s () extensive survey work with WP advisers found little evidence of increasingly personalized services. Kozek and Kubisa's (, p. 121) EU‐level analysis concludes that under the UK government's approach to delivering employability for lone parents ‘personalization involves the identification of those closest to the labour market … issues of gaming, creaming and parking may be the outcomes of such systems, and service options are often limited, focusing predominantly on job search and application processes'.…”
Section: Background To the Researchmentioning
confidence: 99%
See 3 more Smart Citations